Peningkatan Kualitas Layanan Jembatan Jalan Usaha Tani Dusun VI Desa Sambirejo Kecamatan Binjai Kabupaten Langkat Provinsi Sumatera Utara - Mizanuddin Sitompul; Wirdatun Nafiah Putri; Delisma Siregar; Dina Tri Septiningtiyas; Hadianti Muhdinar Pasariibu (Politeknik Piksi Ganesha Indonesia, 2025)
On the agricultural land managed by the Subur Farmers Group, there is one bridge for the farm road. The condition of the bridge is inadequate, in addition to its small dimensions, it has also been severely damaged. The existence of this bridge is very important because it is the only access to the farmer group's agricultural land which is separated by a channel. With this bridge, it can save time and energy in the mobility of agricultural machinery, production facilities and transporting agricultural products from and to agricultural land. The solution offered is to repair the farm road bridge in the form of repairing the river stone masonry and expanding the bridge floor. After this activity, the repair of the farm road bridge can provide adequate access as transportation access in the agricultural area to facilitate the mobility of agricultural machinery, production facilities and transportation of agricultural products from and to agricultural land.